Balance within the Neurexin Trans-Synaptic Connexus Stabilizes Behavioral Control - Clarke, Raymond A.; Eapen, Valsamma (Frontiers in Human Neuroscience, 2014)
Autism spectrum disorder (ASD) is characterised by a broad spectrum of behavioural deficits of unknown aetiology. ASD associated mutations implicate numerous neurological pathways including a common association with the neurexin trans-synaptic connexus (NTSC) which regulates neuronal cell adhesion, neuronal circuitry and neurotransmission. However, there is no apparent correlation between the different competing receptors and ligands of the NTSC and specific behavioural deficits, moreover, comparable DNA lesions affecting the NTSC associate with a diversity of behavioural deficits within and without the autism spectrum, including a very strong association with Tourette syndrome. This lack of a molecular correlation with specific behavioural deficits indicates a more fundamental role for the NTSC in pre-behavioural regulation. A balanced NTSC appears to stabilise behavioural control. The molecular stratification and characterisation of ASD and TS on the basis of NTSC status presents a valuable window for understanding how the NTSC functions in combination with other molecular determinates to strengthen behavioural control and specify behavioural deficits.